SVCT2 Overexpression and Ascorbic Acid Uptake Increase Cortical Neuron Differentiation, Which Is Dependent on Vitamin C Recycling between Neurons and Astrocytes - Katterine Salazar; Francisca Espinoza; Gustavo Cerda-Gallardo; Luciano Ferrada; Rocío Magdalena; Eder Ramírez; Viviana Ulloa; Natalia Saldivia; Ninoschka Troncoso; María José Oviedo; María José Barahona; Fernando Martínez; et al. (MDPI AG, 2021)
During brain development, sodium-vitamin C transporter (SVCT2) has been detected primarily in radial glial cells in situ, with low-to-absent expression in cerebral cortex neuroblasts. However, strong SVCT2 expression is observed during the first postnatal days, resulting in increased intracellular concentration of vitamin C. Hippocampal neurons isolated from SVCT2 knockout mice showed shorter neurites and low clustering of glutamate receptors. Other studies have shown that vitamin C-deprived guinea pigs have reduced spatial memory, suggesting that ascorbic acid (AA) and SVCT2 have important roles in postnatal neuronal differentiation and neurite formation. In this study, SVCT2 lentiviral overexpression induced branching and increased synaptic proteins expression in primary cultures of cortical neurons. Analysis in neuroblastoma 2a (Neuro2a) and human subventricular tumor C3 (HSVT-C3) cells showed similar branching results. SVCT2 was mainly observed in the cell membrane and endoplasmic reticulum; however, it was not detected in the mitochondria. Cellular branching in neuronal cells and in a previously standardized neurosphere assay is dependent on the recycling of vitamin C or reduction in dehydroascorbic acid (DHA, produced by neurons) by glial cells. The effect of WZB117, a selective glucose/DHA transporter 1 (GLUT1) inhibitor expressed in glial cells, was also studied. By inhibiting GLUT1 glial cells, a loss of branching is observed in vitro, which is reproduced in the cerebral cortex in situ. We concluded that vitamin C recycling between neurons and astrocyte-like cells is fundamental to maintain neuronal differentiation in vitro and in vivo. The recycling activity begins at the cerebral postnatal cortex when neurons increase SVCT2 expression and concomitantly, GLUT1 is expressed in glial cells.